1993
DOI: 10.1007/bf00058894
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Amblyseius ovalis (Evans) (Acarina: Phytoseiidae) to natural food resouces and two artificial diets

Abstract: Chain-ing, T. Shih, Chang. H.Y., Hsu, P.H. and Hwang, Y.F., 1993. Responses ofAmblyseius ovalis (Evans) (Acarina: Phytoseiidae) to natural food resources and two artificial diets. Exp. Appl. Acarol., 17: 503-519.Six phytophagous mites, maize pollen, and two artificial diets were fed to Amblyseius ovalis to evaluate their food suitability for the predator. The paraffim diet-chip of Hager and Tassan was adopted for artificial diet studies. The floating leaf method was the best among all tested methods, producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…The majority of phytoseiid mite species that were shown to successfully develop on ADs in previous studies comprised Type III or IV generalists (McMurtry and Scriven 1966;Kennett and Hamai 1980;Itagaki and Koyama 1986;Ochieng' et al 1987;Shih et al 1993). Kennett and Hamai (1980) reported that no individuals of Galendromus occidentalis (Nesbitt) (a Type II phytoseiid mite) developed on an AD composed of yeast components, saccharides, and yolk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of phytoseiid mite species that were shown to successfully develop on ADs in previous studies comprised Type III or IV generalists (McMurtry and Scriven 1966;Kennett and Hamai 1980;Itagaki and Koyama 1986;Ochieng' et al 1987;Shih et al 1993). Kennett and Hamai (1980) reported that no individuals of Galendromus occidentalis (Nesbitt) (a Type II phytoseiid mite) developed on an AD composed of yeast components, saccharides, and yolk.…”
Section: Discussionmentioning
confidence: 99%
“…Although phytoseiid mites (particularly the Type III and IV generalist species) frequently develop, many studies have detected low fecundities of adult females fed artificial diets (McMurtry and Scriven 1966;Kennett and Hamai 1980;Itagaki and Koyama 1986;Ochieng' et al 1987;Shih et al 1993). Because the primary goal of these previous studies was to exploit artificial diets for commercial propagation, experiments in this area have reached a standstill, and the potential for artificial diets to maintain phytoseiid mite populations has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Taiwan, E. ovalis has been studied for future use as a biological control agent, especially regarding its response to different food resources and its predator-prey interactions (Shih et al, 1993;Shih & Wang, 1997). Recently, compared the development and predation rates of Neoseiulus womersleyi (Schicha) and E. ovalis.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns inclusive tem preferência por esse tipo de alimento como é o caso do gênero Euseius e Iphiseius da família Phytoseiidae (McMurtry et al, 2013 Scriven, 1964;Rasmy, 1970;Krishnamoorthy, 1982;Rasmy et al, 1987;Pu et al, 1991;Noronha e Cobo, 1992;Momen, 1995;Reis e Alves, 1997;Vantornhout et al, 2004;Al-Shammery, 2011), Zea mays L. (McMurtry e Scriven, 1964;Kamburov, 1971;Pu et al, 1991;Shih et al, 1993;Afifi et al, 1998;), Typha orientalis Presl (James, 1993), dentre outros.…”
Section: Pólenunclassified